WEB-BASED CONTENT MANAGEMENT SYSTEM - Dobecki, Maciej; Zabierowski, Wojciech (International Journal of Computing, 2010)
This paper describes how to design content management system using the newest web-based techniques. It contains helpful information that can be used during selecting programming language. It introduces multi layer architecture with description and functionality of each layer. It provides description of Model View Controller pattern and how to use it in multi-layer application design. It shows the most powerful Java frameworks that can be applied for each layer and how to connect them in simple way, using Inversion of Control container. It shows power of Spring Framework as business layer, Hibernate as integration layer and ZK Ajax as presentation layer. It proves, that Java combined with applicable libraries can be very powerful tool in good hands.